The Relationship Between Stasys Lozoraitis and the VLIK in 1946–1947 - Jonušauskas, Laurynas (Genocidas ir rezistencija, 2000)
After World War II the relations between the diplomatic corps of Lithuania and the VLIK (Chief Committee for Liberation of Lithuania), the two major Lithuanian political powers in Western Europe, were strained and complicated. During meetings in Bern and Paris held in 1946–1947 the two political bodies tried to establish a mutual understanding on major political discords born of certain political events: the appointment of Stasys Lozoraitis the chief of Lithuania’s diplomatic corps by Minister of Foreign Affairs Juozas Urbšys’ telegram; the Kybartai Act; and the VLIK’s claims to control the diplomatic corps and to direct the actions for Lithuania’s liberation. However, the negotiations between the two political powers were interrupted by the VLAK (Chief Committee for the Restoration of Lithuania’s Statehood), a new political organisation, which maintained contacts with the armed resistance in Lithuania. Lozoraitis held the balance between the VLIK and the VLAK, i.c.. he did not express any preference to either of them. Thus, the efforts to unite the activities of the major political organisations at the meetings in Bern and Paris failed. The organisations for the liberation of Lithuania in Western Europe continued their activities independently.